Prior hip arthroscopy does not affect 1-year patient-reported outcomes following total hip arthroplasty: a register-based matched case-control study of 675 patients - Lindman, Ida; Nåtman, Jonatan; Öhlin, Axel; Svensson Malchau, Karin; Karlsson, Louise; Mohaddes, Maziar; Rolfson, Ola; Sansone, Mikael (Acta Orthopaedica, 2021)
Background and purpose — Femoroacetabular impingement syndrome (FAIS) is a common cause of hip pain and may contribute to the development of osteoarthritis. We investigated whether a prior hip arthroscopy affects the patient-reported outcomes (PROMs) of a later total hip arthroplasty (THA). Patients and methods — Patients undergoing hip arthroscopy between 2011 and 2018 were identified from a hip arthroscopy register and linked to the Swedish Hip Arthroplasty Register (SHAR). A propensity-score matched control group without a prior hip arthroscopy, based on demographic data and preoperative score from the EuroQoL visual analogue scale (EQ VAS) and hip pain score, was identified from SHAR. The group with a hip arthroscopy (treated group) consisted of 135 patients and the matched control group comprised 540 patients. The included PROMs were EQ-5D and EQ VAS of the EuroQoL group, and a questionnaire regarding hip pain and another addressing satisfaction. Rate of reoperation was collected from the SHAR. The follow-up period was 1 year. Results — The mean interval from arthroscopy to THA was 27 months (SD 19). The EQ-5D was 0.81 and 0.82, and EQ VAS was 78 and 79 in the treated group and the matched control group respectively. There were no differences in hip pain, and reported satisfaction was similar with 87% in the treated group and 86% in the matched control group. Interpretation — These results offer reassurance that a prior hip arthroscopy for FAIS does not appear to affect the short-term patient-reported outcomes of a future THA and indicate that patients undergoing an intervention are not at risk of inferior results due to their prior hip arthroscopy